The mystery of the thymus gland. Issue 6 (19th May 2016) - Liu, Daniel; Ellis, Harold
Abstract : The thymus is the last organ in the human body to have its mechanisms fully understood, having had its function fully delineated more than 50 years ago (Miller2004, Tissue Antigens 63:509–517). Prior to this, the thymus gland has had an interesting history with theories having included a role in fetal growth and development before becoming more sinisterly, a cause of sudden infant death in the late 19th century known as status lymphaticus (Paltauf1889, Wien Klin Wochenschr 2:877–881). Until Miller (1961, Lancet 278:748–749) eventually proved its primarily immunological role, the history of this mysterious gland has closely mirrored the history of medicine itself, troubling the minds of pathologists such as Virchow (1872, Ueber die Chlorose und die damit zusammenhängenden Anomalien im Gefässapparate, insbesondere über "Endocarditis puerperalis, " vorgetragen in der Sitzung der Berliner Geburtshülflichen Gesellschaft vom 12) and Grawitz (1888, Deut Med Wochenschr 22:429–431), surgeons such as Astley Cooper (1832, The Anatomy of the Thymus Gland) and Keynes (1953, Ann R Coll Surg 12:88), and eminent medical epidemiologists such as Greenwood and Woods [1927, J Hyg (Lond) 26:305–326]. This article will hopefully be of interest therefore to both clinician and historian alike. Clin. Anat. 29:679–684, 2016. © 2016 Wiley Periodicals, Inc.